2016
DOI: 10.1371/journal.pone.0153644
|View full text |Cite
|
Sign up to set email alerts
|

Regional Deprivation and Non-Cancer Related Computed Tomography Use in Pediatric Patients in Germany: Cross-Sectional Analysis of Cohort Data

Abstract: BackgroundConflicting findings were observed in recent studies assessing the association between patients’ area-level socio-economic status and the received number of computed tomography (CT) examinations in children. The aim was to investigate the association between area-level socio-economic status and variation in CT examination practice for pediatric patients in Germany.MethodsData from Radiology Information Systems for children aged 0 to < 15 years without cancer who had at least one CT examination betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…The findings in our study differed from those in the European and North American studies reporting the use of CT scan by SES, where a highest CT scan use was observed in vulnerable areas compared to the CT scan use in less deprived areas [ 6 9 ]. Head scans were significantly associated to deprivation in the UK study [ 6 ], suggesting that head injuries were the main reason behind the cumulative excess radiation doses received by the study population.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings in our study differed from those in the European and North American studies reporting the use of CT scan by SES, where a highest CT scan use was observed in vulnerable areas compared to the CT scan use in less deprived areas [ 6 9 ]. Head scans were significantly associated to deprivation in the UK study [ 6 ], suggesting that head injuries were the main reason behind the cumulative excess radiation doses received by the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the Dutch study used measures of material deprivation (home income and home value) whereas the Townsend deprivation index used in UK incorporates employment in addition to material deprivation indicators [ 6 , 8 ]. In the Australian [ 4 ], German [ 9 ] and in the present study the indexes used to explain the socioeconomic reality of the study population were more relatable, although the overlapping of the social dimensions included in each index was incomplete.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…SES may confound the association between radiation dose and brain tumor risk in this study as parents of controls tended to have higher education levels (thus, likely, higher level of SES) compared to parents of cases. However, recent reports, show no consistent association between SES and CT-scan exposure [18,[41][42][43][44]. We tested if parental education was related to cumulative dose, and found no association.…”
Section: Discussionmentioning
confidence: 84%
“…The use of CT scans has grown rapidly worldwide in recent decades (1)(2)(3)(4)(5)(6)(7). In 2005, about 8.2 million CT scans were performed in Germany, with a child CT ratio of about 1% (8).…”
mentioning
confidence: 99%